2018
DOI: 10.3389/fmats.2018.00076
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Induced Surface Micro-Deformation of Magnetorheological Elastomers for Roughness Control

Abstract: In this work, we propose mesoscopic model to investigate the surface micro structures of magnetorheological elastomers (MREs) under a magnetic field. By comparing the surface roughness changes of MREs, we found that the surface micro-deformation of MREs, not the field-induced hardness, mainly accounts for the controllable friction characteristics of MREs. The results also demonstrate that the field-induced friction of MREs depends on the particle contents as well as the initial surface roughness. The model pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…By varying the particle number, different particle volume fractions can be achieved. Because of the preparation with an unsmoothed mold, the surface of MRE exhibits a certain roughness, which can be confirmed by our previous study [23]. Therefore, the initial surface microstructure of MRE should be considered in the study of surface morphology changes under the magnetic field.…”
Section: Development Of the Finite Element (Fe) Modelsupporting
confidence: 66%
See 2 more Smart Citations
“…By varying the particle number, different particle volume fractions can be achieved. Because of the preparation with an unsmoothed mold, the surface of MRE exhibits a certain roughness, which can be confirmed by our previous study [23]. Therefore, the initial surface microstructure of MRE should be considered in the study of surface morphology changes under the magnetic field.…”
Section: Development Of the Finite Element (Fe) Modelsupporting
confidence: 66%
“…Recently, some researchers [19][20][21][22] have found that the surface microstructures of MRE will change under the influence of the magnetic field, which provides a new idea for exploring the mechanism of magnetroncontrolled friction of MRE. In previous studies [23], we found that the surface roughness of MRE would change under the action of the magnetic field. However, the observation of MRE surface topography is only from a two-dimensional perspective; thus, the discussion about which factors affect the change trend of roughness is not comprehensive.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The mechanical properties and magnetic controlled deformation of MR materials have been systematically investigated. Due to the tunable mechanical characteristics, MR materials have been widely used in vibration control (Fu et al, 2016;Liu et al, 2019b;Zhang et al, 2019), magnetic sensing (Ding et al, 2018;Ren et al, 2018;Hu et al, 2020), magnetic controlled movement (Lum et al, 2016;Chen et al, 2018;Ubaidillah et al, 2019) and robot manufacturing (Eric et al, 2014;Feng et al, 2017;Vien et al, 2019). In consideration of their easy deformation, tunable mechanical properties and contactless magnetic actuation, the MR materials are expected to have wonderful performance in sound absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the surface properties of MAEs have attracted the attention of several research groups, as it was demonstrated that they can be strongly modulated by applied magnetic fields as well [32,33,34,35,36,37,38,39,40,41]. This interest is driven by a large number of potential applications, ranging from magnetically controllable hydrophobic coatings [33] and biomedical substrates [42] to magnetically reconfigurable diffractive optical elements [34].…”
Section: Introductionmentioning
confidence: 99%